Pelatihan Bahasa Prancis Pariwisata Siswa Jurusan Perhotelan SMK Negeri 1 Kokap Kulonprogo - Rohali, Rohali; Kusnawati, Tri (Faculty of Language and Literature Education, Universitas Pendidikan Indonesia, 2024)
The Community Service (PkM) program for Tourism French Language Training at SMKN 1 Kokap Kulon Progo aimed to introduce and train students from the Hospitality Department. Thirty-six class X students attended the training, which covered topics such as introducing oneself and greeting guests, room and food reservations, and front office and room service practices. The training was conducted using various methods such as lectures, discussions, role playing, and practical work in the laboratory. The results showed high interest and enthusiasm among students, and they were able to practice dialogue related to booking rooms and food, as well as front office and room service skills. Feedback from a questionnaire regarding the PkM implementation indicated high scores in terms of the team's ability to carry out activities, learning effectiveness, the taught material, and its usefulness.